Penerapan Bangunan Hijau Pada Kawasan Kantor Terpadu Pt. Hki Di Gebang - Sari, Indah Novita (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2023)
The issue of global warming has recently been increasingly being discussed, so that people need a balanced source of energy and natural resources. Indonesia is one of the countries that has joined the movement to go green or reforestation as an activity to save the earth from damage due to global warming issues and change lifestyles to care more about the surrounding environment. The application of Green Buildings is the solution to the problem. This study discusses the application of green building principles in the integrated office area of PT. HKI in Gebang. Integrated office of PT. HKI in Gebang is the head office for all sections of the Trans Sumatra toll road project zone, Binjai–Langsa Section. Located on the Medan-Aceh crossroad, Gebang District, Langkat Regency, North Sumatra. The purpose of this research is that humans will try to use as few resources as possible to improve the quality of life of present and future generations so that they can use the earth's resources for a long time, of course this requires the response and cooperation of all parties so that the building concept green can go according to plan. The implementation of this research is very important to describe the picture of future plans.